Magnetic surfactants - Brown, P.; Alan Hatton, T.; Eastoe, J. (Current opinion in colloid & interface science, 2015)
Surfactants are ubiquitous, being important commodity chemicals with wide industrial applications, and essential components of living organisms. With stimuli-responsive surfactants, self-assembly and physicochemical properties of a wide variety of materials may be readily manipulated, both reversibly and irreversibly. Until recently, magnetically responsive surfactants had not been reported. This review reports the recent progress in magnetoresponsive surfactants, covering control of interface and bulk solution properties. The use of these magneto-surfactants as novel molecular magnets is reported, and potential applications are identified. [Display omitted] •Introduce the 3 existing classes of magnetic surfactants; ionic, coordinating, covalently bound.•Consider a potential 4th class of magnetic surfactant.•Describe how these surfactants function as molecular magnets.•Report potential applications ranging biochemistry to water treatment.•Discuss the origins of magnetism in dilute aqueous solutions.